ANTICARDIOLIPIN ANTIBODIES IN WOMEN HAVING RECURRENT SPONTANEOUS ABORTIONS - Khoharo, Haji Khan; Nizamani, Ghulam Shah; Memon, Rashid Ahmed; Kazi, Navaid; Kazi, Sumayya (Pakistan Journal of Physiology, 2015)
The present study was conducted to analyze Anticardiolipin antibodies in women with recurrent spontaneous abortion. Methods: This was a case control study conducted from January to December 2013. A sample of 136 women, comprising of 68 cases and equal number of controls was selected according to inclusion and exclusion criteria. Strict history protocol was mandatory for women with recurrent spontaneous abortions. Women with history of immune, rheumatic, endocrine and thrombo-embolic disorders were excluded. Patients were selected through non-probability purposive sampling. Anticardiolipin antibodies were estimated by ELISA method. Data were analysed on SPSS-21. Results: Anticardiolipin antibodies were detected in 16.19% and 4.41% in cases and controls respectively. Mean serum levels of anticardiolipin antibodies were 9.15Â±3.73 and 7.35Â±2.74 RU/ml respectively. Platelet counts, prothrombin and activated partial thromboplastin revealed no significant differences between groups. Conclusion: Anticardiolipin antibodies were detected in women with recurrent spontaneous abortions.